Implementation of Artificial Intelligence and Big Data to Overcome Covid-19 Pandemic - Christopher Jody Widiyono; Joni Maulindar (Proceeding of International Conference on Science, Health, And Technology, 2021)
At this time, where the COVID-19 pandemic caused by a new type of corona virus is occurring, the demands in the health sector are becoming heavy. Seeing the increasing number of confirmed cases of COVID-19 patients and the number of existing cases of death, a solution is needed to deal with this crisis. Artificial Intelligence and Big Data are technologies that can be adapted to deal with the COVID-19 pandemic. This review will discuss how technology based on Artificial Intelligence and Big Data can be implemented to help medical personnel carry out initial diagnoses and various kinds of research to assist drug and vaccine discovery.